'Drawing in' other worlds: Addressing fragile heritage landscapes through cosmopolitical maps. Issue 2 (3rd April 2021) - Hussain, Zahra
ABSTRACT: This paper builds on the argument that large-scale infrastructural development in remote communities poses a threat to their local heritage landscape. This is done not only through physical intervention in landscapes (through bridges, roads, pipelines or ports) but also through imaginaries projected about development that tends to re-label local landscapes as hotspots for development. This paper explores drawing as a medium to explore fragile-heritage landscapes through the stories, folklores and experiences of local communities within their landscape. It proposes a mapping strategy that attempts to grasp the diminishing heritage landscapes of Gwadar, a coastal town in Pakistan which is being re-claimed as the hub of prosperity (port) connecting two infrastructural mammoths: the BRI land routes and maritime silk roads. Together with the community, their stories and memories, we 'draw-in' tangible, immaterial, invisible, human, spiritual and more-than-human entities, and their worlds that are at risk of erasure in the current wave of infrastructural development.